The ventilatory threshold, heart rate, and endurance performance: relationships in elite cyclists - Hoogeveen, A. R.; Hoogsteen, G. S. (International Journal of Sports Medicine, 1999)
The purpose of this study was to investigate the validity of the ventilatory response during incremental exercise as indication of endurance performance during prolonged high-intensity exercise under field test conditions in elite cyclists. The ventilatory threshold (VT) was assessed in 14 male elite cyclists (age 22.4+/-3.4 years, height 181+/-6 cm, weight 69.2+/-6.8 kg, VO2max 69+/-7 ml x min(-1) x kg(-1)) during an incremental exercise test (20 W x min(-1)). Heart rate and oxygen uptake were assessed at the following ventilatory parameters: 1. Steeper increase of VCO2 as compared to VO2 (V-slope-method); 2. Respiratory exchange ratio (RQ)=0.95 and 1.00; 3. VE/VO2 increase without a concomitant VE/VCO2 (VE/VO2 method). Three weeks following the laboratory tests, the ability to maintain high-intensity exercise was determined during a 40 km time trial on a bicycle. During this time trial the mean heart rate (HR(TT)) and the road racing time (TT) were assessed. The V-slope-method and the VE/VO2 method showed significant correlations with TT (V-slope: r = -0.82; p<0.001; 90% interval of confidence = +/-82 sec; VE/VO2: r=-0.81; p<0.01; 90% interval of confidence = +/-81 sec). Heart rate at the ventilatory parameters and at the maximum heart rate (HRmax) showed significant correlations with HR(TT). The V-slope-method is the preferred method to predict heart rate during prolonged high-intensity exercise (r=0.93; p<0.0001; 90% interval of confidence: +/-4.8 beats x min(-1)). For predicting heart rate during prolonged high-intensity exercise using an incremental exercise test (20 W x min(-1)), without the knowledge of ventilatory parameters, we recommend using the regression formula: H(TT)=0.84 x Hmax + 14.3 beats x min(-1) (r=0.85; p<0.001).